Identification of oil palm root-specific genes through mining of RNA-Seq data and RT-qPCR analysis - Subhi, Siti Masura; Omar, Abd Rasid; Shaharuddin, Noor Azmi; Abdul Masani, Mat Yunus; Chan, Kuang Lim; Low, Eng Ti Leslie; Badai, Siti Suriawati; Ayub, Nor Hanin; Abdul Rahman, Siti Rahmah; Abdullah, Mohd Puad; Mohamad Azzeme, Azzreena; Ahmad Parveez, Ghulam Kadir (Malaysian Palm Oil Board, 2021)
Identification of novel genes that are specifically expressed in root is essential for isolation and characterisation of root-specific promoters. Mining the transcriptome of various oil palm tissue-specific data generated from ribonucleic acid-sequencing (RNA-Seq) technology has enabled the discovery of root-specific genes. A total of seven candidates of root-specifically or preferentially expressed genes were selected from RNA-Seq analysis, and the gene expression profiles were validated using real-time quantitative polymerase chain reaction (RT-qPCR). The relative fold change of transcript expression in RT-qPCR was statistically analysed by comparing with root tissues at the in vitro culture stage (RS1). Results showed that the transcript annotated as an oil palm metallothionine (EgMT) gene was significantly upregulated at around 7 to 170-fold across the different developmental stages of root tissues. A proline-rich protein (EgPRP1) transcript was also significantly upregulated by about 7 to 55-fold. Both EgMT and EgPRP1 transcripts had relatively low expressions in the other tissues studied. The high levels of expression of EgMT and EgPRP1 in roots highlighted the genes’ promoter’s potential to regulate a strong expression level of transgenes in a root-specific manner.